Penggunaan Platform Crowdfunding dalam Upaya Peningkatan Penghimpunan Dana Zakat Infak dan Sedekah di LAZ Lidzikri Bandung - Fatimah, Risi Siti; Suryaman, Maman (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine the strategy for using the crowdfunding platform in an effort to increase fund collection, and to determine the implications of using the crowdfunding platform in an effort to increase the collection of ZIS funds at LAZ Lidzikri Bandung. This research uses field research and a qualitative approach. And the data collection techniques used are interview, observation and documentation techniques. Interviews were conducted directly with the fund raiser, deputy head of the institution, and head of the institution. Collect information in the form of photos, data and other documents. This research uses data analysis with an inductive method. The conclusion of this research is that the Amil Zakat Lidzikri Bandung Institute has started implementing crowdfunding or raising funds through digital technology. And the implications of crowdfunding implemented at LAZ Lidzikri have had a positive influence in increasing the number of donors and funds.